MARX'S PROMETHEAN HUMANISM - Abraham, Kuruvilla C (Journal of Dharma, 1989)
A spectre is haul'lting Europe-the spectre of Comrnunisrn,? When Karl Marx wrote those words in 1848, little did he realize that a century later that 'spectre' would be haunting the whole world 'in a form resembling only in outline the plan of its former rnaster.? For world-wide Communism today includes millions of people from a variety of religious, cultural, racial and geographical backgrounds and in its local manifestations the message of Marx has merged with elements of cultures they represent. 'Red monks and hajjis were and are commonplace in many parts of rural Southeast Asla.? Nationalist leaders in many countries in Asia and Africa forged Marxist doctrine into a powerful weapon for their attacks on colonialism and imperialism.